Genomic analysis, culturing optimization, and characterization of Escherichia bacteriophage OSYSP, previously studied as effective pathogen control on fresh produce - Yesil, Mustafa; Huang, En; Yang, Xu; Yousef, Ahmed E. (Frontiers in Microbiology, 2024)
Advances in bacteriophage genome sequencing and regulatory approvals of some bacteriophages in various applications have renewed interest in these antibacterial viruses as a potential solution to persistent food safety challenges. Here, we analyzed in depth the genome of the previously studied Escherichia bacteriophage OSYSP (phage OSYSP), revealed its application-related characteristics, and optimized its enumeration techniques for facilitating industrial implementation. We previously sequenced phage OSYSP genome completely by combining results from Illumina Miseq and Ion Torrent sequencing platforms and completing the remaining sequence gaps using PCR. Based on the genomics analysis completed herein, phage OSYSP was confirmed as an obligate lytic phage of the Caudoviricetes class. The genome encodes 81 proteins of identifiable functions, including two endolysins and 45 proteins that support host-independent DNA replication, transcription, and repair. Despite its similarities to T5-like phages, unique genome arrangements confirm phage OSYSP’s novelty. The genomic analysis also confirmed the absence of DNA sequences encoding virulence or antibiotic resistance factors. For optimizing phage detection and quantification in the conventional plaque assay, it was observed that decreasing the concentration of agar or agarose, when used as a medium gelling agent, increased phage recovery (p < 0.05), but using agarose resulted in smaller plaque diameters (p < 0.05). Phage OSYSP inactivated pathogenic and non-pathogenic strains of E. coli and some Salmonella enterica serovars, with more pronounced effect against E. coli O157:H7. Phage titers remained fairly unchanged throughout a 24-month storage at 4°C. Incubation for 30 min at 4°C−47°C or pH 4–11 had no significant detrimental effect (p > 0.05) on phage infectivity. In vitro application of phage OSYSP against E. coli O157:H7 EDL933 decreased the pathogen’s viable population by >5.7-log CFU/mL within 80 min, at a multiplicity of infection as low as 0.01. The favorable genome characteristics, combined with improved enumeration methodology, and the proven infectivity stability, make phage OSYSP a promising biocontrol agent against pathogenic E. coli for food or therapeutic applications.